Capital structure pre-balancing: Evidence from convertible bonds - Rastad, Mahdi (Journal of Corporate Finance, 2016)
A large body of the corporate finance literature is devoted to capital structure. This literature examines whether firms have a target capital structure, and whether they actively rebalance their capital structure toward a target. Since conversion of a convertible bond causes a drop in leverage, target capital structure theory suggests that the structure should be rebalanced in the future. I consistently find that following a realized conversion firms rebalance their positions in less than a year. When the stock price passes the conversion price threshold for a convertible bond, the firm expects this drop in leverage to occur in the near future. Using a regression discontinuity design around the conversion price threshold for those conversions that are decided by investors, not by the firm, my paper documents a 20% increase in leverage before an actual drop in leverage. That is to say, firms do not wait for the realization of leverage shocks but rather respond to anticipated shocks. A quantile treatment effect analysis reveals the effect to be a hump-shaped function of leverage, with a peak for firms with a conditional leverage ratio around the 70th percentile.